Thermal Simulation of Power Supply System for Train - XIE Haibo; DING Jie; LIU Yong; LI Biyu; GE Huijun (Kongzhi Yu Xinxi Jishu)
With the number of train electrical equipment increasing, the thermal loss power of power supply system is also growing. To test whether the performance of the cooling system of train power supply system can meet the requirements, by using Icepak software, finite volume method and zero-equation turbulence model, solving three-dimensional N-S equation and calculating three-dimensional temperature field model, the temperature distribution of transformer and converter module and the flow field distribution of the cabinet were obtained. Based on experimental verification, the simulation results of temperature distribution are consistent with experimental results, and the single-point temperature differentials between the simulation and the test results are allowable.